ROLE OF THE CLASS TEACHER IN COUNSELING SERVICES AT SD NEGERI TEUPIN BATEE ACEH TIMUR - Pipit Agustri Rahayu; Akmaluddin; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research departs from the background that guidance and counselingservices in elementary schools are still not optimally carried out by the school,so that students' problems are difficult to understand and overcome. Aiming todescribe the role of elementary school teachers in guidance and counselingservices, researchers used a qualitative research method with an essentialphenomenological design. The research subject was a class teacher at SDNegeri Teupin Batee Aceh Timur. Focusing on optimal teacher experience andawareness in the daily guidance and counseling process, this study concludesthat elementary schools do not have special guidance and counseling teachers,but this does not mean that counseling services are not implemented inelementary schools. However, it is the class teacher who contributes toproviding these guidance services supported by the principal and others. Theteacher plays a very important role in providing guidance and counselingservices to children, the teacher really has to understand each of his students sothat students get appropriate and targeted assistance.